2020
DOI: 10.3390/foods9121790
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gluten in Dried Yeast and Yeast-Containing Products

Abstract: Yeast are commonly used in the preparation of foods and beverages such as beer and bread and may also be used on their own as a source of nutrients and flavoring. Because of the historical connection of yeast to products made from wheat and barley, consumers maintaining a gluten-free diet can have concerns about the safety of yeast ingredients. Analyzing the safety of yeast and yeast-containing products presents some difficulties, as the yeast organisms actively degrade any gluten in the product, raising quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Brewer's yeast is known to contain residual levels of gluten from beer brewing. A study from Allred et al reported dried brewers' yeast to have a gluten content exceeding 270mg/kg [31], offering an explanation to the gluten detected in the honey samples. It is known caseins account for the majority (80%) of total milk protein [42], so it is surprising to detect less casein allergen than whey allergen present in the honey samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brewer's yeast is known to contain residual levels of gluten from beer brewing. A study from Allred et al reported dried brewers' yeast to have a gluten content exceeding 270mg/kg [31], offering an explanation to the gluten detected in the honey samples. It is known caseins account for the majority (80%) of total milk protein [42], so it is surprising to detect less casein allergen than whey allergen present in the honey samples.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary feeding is one of the Beekeeping Management Practices implemented by beekeepers to maintain healthy honeybee colonies and to achieve agricultural and food production objectives. In some cases, Beekeepers tend to supplement with mixtures of soybean flour, dried brewer's yeast (which is known to contain gluten [31]), and dry skimmed milk with sugar and water [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Yeasts are a group of unicellular microorganisms that can propagate by budding or cleavage, and both survive in aerobic and anaerobic environments. The use of yeast can be traced back to four thousand years ago [ 81 ] in brewing, food and pharmaceutical industries, usually for fermentation, beer brewing, and alcohol manufacturing. Yeasts consisting of numerous proteins and vitamins that can not only be used as medicinal yeast tablets and feed additives, but also as an ideal raw material for the production of single‐cell protein, extraction and preparation of nucleotide, coenzyme A, cytochrome C, and amino acids.…”
Section: Biofermentation Technology For Synthesis Of Bc‐based Materialsmentioning
confidence: 99%
“…Additionally, it is recognized that Y. lipolytica protein biomass is gluten-free. It is proven that the nutritional yeast products, i.e., the protein biomass, contained gluten at below the 20 mg/kg threshold defined by the Codex Alimentarius, The Codex, or the Gluten-Free Certification Organization (GFCO) [ 213 ].…”
Section: Safety Of Y Lipolytica As a Valuable Sour...mentioning
confidence: 99%